Response to Glenn - Arons, Stephen (Education Policy Analysis Archives, 1998)
Arons responds to what he considers to be Glenn's misrepresentations of the tone and content of Short Route To Chaos. He writes that Glenn "appears to be attempting to construct the book's message into just one more salvo fired in the endless school wars. It is anything but....Reading Glenn's review, one is left with the impression that the book is a Christian-bashing, left-leaning, work of communitarian fuzziness in which a legal scholar unaccountably refuses to confine himself to ... technical explication of existing constitutional doctrine." In his response, Arons affirmatively sets out some of the book's main themes of political /cultural conflict over standardized schooling, corrects some of what he sees as Glenn's misunderstandings, and notes that the book itself invites readers to eschew partisanship and recognize that there are deep structural problems in American public education. In closing, Arons uses an example of Glenn's partisan misunderstanding that leads Arons to recommend to the reader that it would be better to read Short Route to Chaos for oneself.